PENGARUH JIGSAW TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN TEKS EKSPLANASI DI SMKN 1 PAYAKUMBUH - Azizah, Jamil; Ratna, Ellya; Hafrison, Mohammad (Universitas Negeri Padang, 2018)
ABSTRACTÂ This study aims to describe the effect of cooperative learning model type jigsaw on reading comprehension skills of explanatory text of students of class XI SMKN 1 Payakumbuh. The data in this research are two, namely the comprehension text reading comprehension skills before using the jigsaw type cooperative learning model obtained through objective test of 33 items and tested on May 14, 2018 and skill reading comprehension text data after using jigsaw type cooperative learning model obtained through objective test of 33 items and tested on May 17, 2018. Based on the research, it can be concluded that cooperative learning model of jigsaw type can be used as an alternative of learning comprehension reading comprehension skills of school text.Â Kata kunci: pengaruh, model pembelajaran kooperatif tipe jigsaw, membaca pemahaman, teks eksplanasi